Effectiveness of Glaucoma Counseling on Rates of Follow-up and Glaucoma Knowledge in a South Indian Population - Do, Anna T.; Pillai, Manju R.; Balakrishnan, Vijayakumar; Chang, Robert T.; Robin, Alan L.; Singh, Kuldev; Lee, Bradford W. (American journal of ophthalmology, 2016)
To evaluate the impact of traditional counseling and patient-centered counseling, either alone or with recorded audio counseling reinforcement, on glaucoma knowledge and clinical follow-up. Prospective randomized controlled trial. Newly diagnosed adult glaucoma patients were randomized to 1 of 3 categories of glaucoma counseling: traditional counseling, patient-centered counseling, or patient-centered counseling with audio counseling reinforcement. Demographic and clinical information from each subject was ascertained, and all subjects completed the Glaucoma Knowledge Assessment before and after counseling sessions at the time of diagnosis and at 1-month follow-up. Patients were instructed to return to clinic for routine follow-up at 1, 3, 6, 9, and 12 months after enrollment. A multivariate logistic regression model was used to determine factors associated with appropriate clinical follow-up. Overall, only 13.5% of subjects had appropriate clinical follow-up at 1 year, defined as attending at least 3 follow-up visits during that interval, and there was no significant difference between counseling groups. The mean glaucoma knowledge assessment score (GKAS) improved by 77.6% with the initial counseling intervention (P < .0001), decreased by 17.4% within a 1-month period following initial counseling, and improved by 22.8% (P < .001) after the second counseling intervention. Monthly household income over 2500 rupees, GKAS greater than 5 after initial counseling, and undergoing any ocular surgical procedure were all independent predictors of appropriate follow-up. While all 3 counseling methods resulted in transient improvement of patient knowledge regarding glaucomatous disease, follow-up rates were poor for all groups. Poor retention of glaucoma knowledge may impact the likelihood of patient follow-up, and reinforcement with repeated counseling may be beneficial with regard to both disease knowledge and follow-up.